Fiqih Islam perspektif dialektika sosiologi pengetahuan: studi pemikiran hadis al-Shafi'i - Muhammad Irfan Helmy (Ijtihad : Jurnal Wacana Hukum Islam dan Kemanusiaan, 2011)
The study of prophetic tradition which focuses on socio-historical perspectives must be conducted to explore a new perspectives of prophetic tradition studies. The science of Contradictive prophetic tradition which established by al-Syafii is a part of prophetic tradition sciences which can be analyzed with socio-historical perspectives. This article used a sociology of knowledge dialectic approach to find a socio-historical background of establishment of the Science of Contradictive prophetic tradition. This approach conclude that the framework of al-Syafii's Science of Contradictive prophetic tradition influenced by many thought on prophetic tradition which arose in al-Syafii's life especially the destructive one to the position of prophetic tradition in Islam. According to sociology of knowledge perspective, al-Syafii's science of Contradictive prophetic tradition must be open to receive a new contribution of methodology of prophetic tradition understanding.